2021
DOI: 10.1061/(asce)sc.1943-5576.0000575
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Building Resistance to Differential Settlement with Canadian Seismic Design Provisions

Abstract: Enhancing Building Resistance to Differential Settlement with Canadian Seismic Design Provisions Romaric Léo Esteban DesbroussesThis research project focuses on evaluating the influence of Canadian seismic design provisions on the resistance of reinforced concrete buildings against the differential settlement of their foundation. Three types of moment-resisting frame buildings located Vancouver, Montreal and Toronto are designed in accordance with the latest editions of the National Building Code of Canada and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…They reported that buildings with a shorter span length are more vulnerable to settlement-induced damage than buildings with longer spans. A nonlinear analysis was performed on a center column to a settlement of 100 mm (Romaric Leo and Lan Lin, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that buildings with a shorter span length are more vulnerable to settlement-induced damage than buildings with longer spans. A nonlinear analysis was performed on a center column to a settlement of 100 mm (Romaric Leo and Lan Lin, 2021).…”
Section: Introductionmentioning
confidence: 99%